2016
DOI: 10.1128/jcm.01410-16
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Independent Detection of Nontuberculous Mycobacteria in Clinical Respiratory Samples

Abstract: f Culture-based detection of nontuberculous Mycobacteria (NTM) in respiratory samples is time consuming and can be subject to overgrowth by nonmycobacterial bacteria. We describe a single-reaction TaqMan quantitative PCR assay for the direct detection of NTM species in clinical samples that is specific, sensitive, and robust. While rates of infection caused by members of the Mycobacterium tuberculosis complex continue to fall in developed countries (1, 2), disease caused by nontuberculous mycobacteria (NTM) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Similar molecular methods to those used in species identification may be applied to DNA extracted from respiratory samples to directly detect and identify NTM without the need for culture [128][129][130][131][132][133]. However, the reported sensitivity is low, detecting NTM in only 29-76% of culture positive samples [128][129][130]132], although better detection rates are reported in more heavily smear-positive samples.…”
Section: Culture-free Ntm Detectionmentioning
confidence: 99%
“…Similar molecular methods to those used in species identification may be applied to DNA extracted from respiratory samples to directly detect and identify NTM without the need for culture [128][129][130][131][132][133]. However, the reported sensitivity is low, detecting NTM in only 29-76% of culture positive samples [128][129][130]132], although better detection rates are reported in more heavily smear-positive samples.…”
Section: Culture-free Ntm Detectionmentioning
confidence: 99%
“…However, several species may not be differentiated as there is not enough genomic divergence to allow for accurate diagnosis beyond species complex level. Similar to MALDI-TOF, test characteristics depend on the library of available sequences [19] .…”
Section: Diagnosing Non-tuberculous Mycobacteria Infectionsmentioning
confidence: 99%
“…This would subject patients to unnecessary toxic treatment and may promote resistance. However, this limitation is mitigated by pairing the molecular diagnostic test, which has high specificity [18] , to a previous culture, and confirming concordance of the results. This strategy, when applied in conjunction with the appropriate clinical context, should limit over-treatment.…”
Section: Introductionmentioning
confidence: 84%
“…Sequencing these regions allows for an additional spectrum of less frequently isolated NTMs to be identified and not included in commercial kits. The benefit of using these genes for detecting NTMs over traditional diagnostic culture-based methods is highlighted in a study performed on respiratory specimens in which quantitative PCR of the hsp65 gene identified three NTMs (two M. avium and one M. flavescens ) reported as culture-negative [18] . A recent approach employed a combination of loop-mediated isothermal amplification and lateral flow biosensors, specifically targeting the rpoB gene of M. kansassi .…”
Section: Introductionmentioning
confidence: 99%